Caught in the Crunch: School District Financial Condition and Performance. (June 2019) - Kim, Youngsung; Sorensen, Lucy C.
The ability of public organizations under fiscal stress to achieve their goals and maintain public service delivery warrants attention. Using an eleven-year panel of school-district data from New York State, this study examines how different dimensions of financial condition affect district performance. The findings indicate that increasing debt burdens have immediate negative impacts on school-district performance. These adverse impacts may be driven by the cutback strategies that districts choose in response to declining financial conditions. These findings have practical implications for how public organizations can best cope with rising debt while maintaining high performance.